2017
DOI: 10.1209/0295-5075/119/67002
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of charge screening in Fe/SrTiO 3 heterostructure

Abstract: The modulation of magnetization as a function of the temperature was studied in the Fe/SrTiO3 heterostructure by the electric field reversal. The magnetization is strong when the SrTiO3 layer is at the accumulation state but, when the SrTiO3 layer is at the depletion state, the magnetization of the Fe layer is weak. This phenomenon can be qualitatively explained by the variation in the electronic spin density of the Fe layer near the interface under reversing electric fields. The decrease in the change of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The in-plane M-H loops of the two heterostructures tested at 200 K under various electric fields are shown in figures 6(a) and (b), respectively. It is worth noting that the chargemediated ME response is weak at high temperature [25,29], so that the selected test temperature is much lower than room temperature. It is found that the saturation magnetization (M s ) at +300 kV cm −1 exhibits a noticeable increase with respect to that with no applied electric field at the maximum magnetic field of 5 kOe.…”
Section: Resultsmentioning
confidence: 99%
“…The in-plane M-H loops of the two heterostructures tested at 200 K under various electric fields are shown in figures 6(a) and (b), respectively. It is worth noting that the chargemediated ME response is weak at high temperature [25,29], so that the selected test temperature is much lower than room temperature. It is found that the saturation magnetization (M s ) at +300 kV cm −1 exhibits a noticeable increase with respect to that with no applied electric field at the maximum magnetic field of 5 kOe.…”
Section: Resultsmentioning
confidence: 99%
“…The VT at the T V involves a random distribution of Fe 3+ and Fe 2+ ions opposed to a charge ordered one on the B sites showing charge localization [29]. The magnitude of the charge screening effect has a strong correlation with temperature and increases with temperature decreasing [32]. But the magnitudes of the change in saturation magnetization generated by the applied voltages are almost the same above and below the T V and, as shown in figure 3(b), even the change above the T V is slightly greater than that below the T V .…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Vaz et al [8] and Tian et al [9] have demonstrated the temperature-dependent magnetism tuned by the strain effect. The charge effect evolving with the temperature has been explored in multiferroic heterostructures of Fe/SrTiO 3 and PbZrTiO 3 /LaSrMnO 3 [10,11]. Of particular interest is exploiting phase transitions stimulated by changing temperature.…”
Section: Introductionmentioning
confidence: 99%